2022
DOI: 10.1080/10717544.2022.2120925
|View full text |Cite
|
Sign up to set email alerts
|

Pitavastatin-loaded bilosomes for oral treatment of hepatocellular carcinoma: a repurposing approach

Abstract: Albeit its established efficacy as an anti-hyperlipidemic agent, pitavastatin (PIT) has been shown to have other various therapeutic effects. One of these effects is the anti-cancer activity against hepatocellular carcinoma (HCC). This effect has been evaluated in this study for the first time via its oral delivery loaded in bilosomes both in vitro in hepatocellular carcinoma (HCC) cell line; HepG2 and in vivo in an Ehrlich ascites carcinoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 72 publications
(90 reference statements)
0
9
0
Order By: Relevance
“…The small size of these vesicles confirms that bilosomal vesicles are effective nano-carriers for delivering Sulpiride through the skin. Zeta potential is a measurable characteristic that may be utilized for predicting the physical stability of the vesicular formulations [35]. In our study, the zeta potential of the optimized formulation (Su-BLs) was measured to be −26.9 ± 1.4 mV, as displayed in Figure 3c.…”
Section: Physicochemical Characterization Of the Optimized Su-bls 231...mentioning
confidence: 79%
“…The small size of these vesicles confirms that bilosomal vesicles are effective nano-carriers for delivering Sulpiride through the skin. Zeta potential is a measurable characteristic that may be utilized for predicting the physical stability of the vesicular formulations [35]. In our study, the zeta potential of the optimized formulation (Su-BLs) was measured to be −26.9 ± 1.4 mV, as displayed in Figure 3c.…”
Section: Physicochemical Characterization Of the Optimized Su-bls 231...mentioning
confidence: 79%
“…This may be attributed to the difference in the structure of the two bile salts used, where the bulkier SC (430.6 g/mol) led to the formation of bilosomes with a larger PS in comparison to the less bulky SDC (414.56 g/mol) [ 65 ]. This difference between SDC and SC formulations might also be ascribed to the presence of one additional OH group in SC compared to SDC, which exerted an additional steric hindrance on the formed vesicle surface and resulted in the difference in the PS values of the two types of vesicles [ 66 , 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was revealed that the formulations prepared using SDC had significantly higher absolute ZP values than those prepared by SC, as shown in the Supplementary File (Figure S2a) . This difference in ZP values between SDC and SC formulations might be attributed to the presence of one additional OH group in SC compared to SDC, which might lead to the difference in the ZP values [ 66 , 67 , 74 , 75 ]. By examining the effect of the amount of bile salt used (Factor B), it was also obvious that increasing the amount of bile salt from 5 to 10 mg significantly increased the ZP ( p < 0.01) value, as shown in Figure S2b in the Supplementary File due to the increase in the anionic charge on the prepared vesicles.…”
Section: Resultsmentioning
confidence: 99%
“…This highlights the potential of NS surface modification with LF to improve the anticancer activity of FS via an active targeting mechanism. Indeed, LF-targeted formulations have previously shown higher anticancer activity compared to both free drug and untargeted nanotherapy [ 33 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Fisetin entrapment efficiency% (EE%) was carried out using the dialysis technique [ 33 ]. FS-NS and LF-FS-NS dispersions (0.5 mL) were placed in a dialysis bag (Visking 36/32, 28 mm, MWCO 12–14 KDa; Serva, Heidelberg, Germany) and then immersed in 26 mL PBS (pH 7.4) containing 0.1% Tween ® 80 to maintain sink conditions, before being centrifuged at 25 °C and 500 rpm for 30 min using a high-speed cooling centrifuge (Model 3K-30; Sigma Laborzentrifugen GmbH, Osterode, Germany).…”
Section: Methodsmentioning
confidence: 99%